Legal education on bank responsibilities and customer vigilance in maintaining the security of savings funds for the community (Case study of PT Bank Sulteng, Palu City) - Eva Palampanga; Fajriani Amalia; Dea Manuhulu; Gabriella Almasari Datuan; Harun Harun (PT WIM Solusi Prima, 2026)
Public trust is the primary foundation of banking activities, particularly regarding the security of customer deposits. However, in practice, various problems such as lost funds, account breaches, and system failures that result in losses for customers are still encountered. This study aims to examine and provide legal education regarding banks' legal responsibilities for the security of customer deposits based on the provisions of Indonesian laws and regulations. The research method used is normative legal research with a statutory and conceptual approach. The results show that banks have a legal obligation to maintain the security of customer funds as part of the prudential principle and consumer protection. This responsibility is regulated by various regulations, including the Banking Law, provisions of supervisory authorities, and principles of consumer protection for financial services. If a loss occurs due to negligence or error on the part of the bank, the bank is obliged to provide compensation to the customer. Therefore, legal education for the public is important so that customers understand their rights and available legal protection mechanisms. This research is expected to contribute to increasing legal awareness and strengthening public trust in the banking system.